(untitled) (Journal of Economic Research & Business Administration, 2015)
In the innovation economy are questions related to the formation and development of the intellectual capital of the organization. Effective use of intellectual capital ensures the competitiveness of the organization , provides additional income due to the unique competitive advantages. Particular attention is paid to study the reasons hindering the development of intellectual capital in our country is the low quality of the institutional environment , distorted the mechanisms of market competition , the deformation mechanisms of accumulation, inefficient system of state regulation of innovation these and other problems in modern conditions hamper the development of intellectual capital. The main source of positive growth value of the company is to increase the value of intellectual capital , which is formed based on the commercialization of intellectual property and other intangible assets.